Critical thinking in national tests across four subjects in Swedish compulsory school. Issue 1 (2nd January 2019) - Nygren, Thomas; Haglund, Jesper; Samuelsson, Christopher Robin; Af Geijerstam, Åsa; Prytz, Johan
ABSTRACT: Critical thinking is brought to the fore as a central competence in today's society and in school curricula, but what may be emphasised as a general skill may also differ across school subjects. Using a mixed methods approach we identify general formulations regarding critical thinking in the Swedish curriculum of school year nine and seven more subject-specific categories of critical thinking in the syllabi and national tests in history, physics, mathematics and Swedish. By analysing 76 individual students' critical thinking as expressed in national tests we find that a student that thinks critically in one subjects does not necessarily do so in other subjects. We find that students' grades in different subjects are closely linked to their abilities to answer questions designed to test critical thinking in the subjects. We also find that the same formulations of critical thinking in two subjects may mean very different things when translated into assessments. Our findings suggest that critical thinking among students comprise different, subject-specific skills. The complexity of our findings highlights a need for future research to help clarify to students and researchers what it means to think critically in school.